The growzen™ buddy smartphone app to improve adherence in patients receiving recombinant human growth hormone therapy: a retrospective observational study in Argentina - van Dommelen, Paula; Arnaud, Lilian; Assefi, Aria Reza; Crespo, Maria Lourdes; Debicki, Matias; Michelis, Fulvio; Koledova, Ekaterina (Frontiers in Endocrinology, 2024)
This study in Argentina evaluated the impact of the growzen™ buddy smartphone app on adherence to recombinant human growth hormone (r-hGH) treatment. Adherence data, invitation dates with a link to the app, app activation dates, and height measurements entered were extracted from the growzen™ digital health ecosystem. Patients with 12 months of adherence data, aged ≥2 years at treatment start, and aged <19 years were selected both before and after app implementation. Mean adherence was classified as optimal (≥85%) versus suboptimal (<85%). Adherence before and after implementation and the pre-post effect on adherence were assessed. Data for 830 patients were available. Prior to app implementation, the proportion of patients with optimal adherence was 68% (n=348/515). Following app implementation, out of 315 patients, 302 (96%) received an invitation with a link to the app, 225 (71%) activated their account, and 127 (40%) entered height data in the first year. There was a significant early increase in the proportion of patients with optimal adherence following implementation: 82% (n=258/315), p<0.001. After implementation, the proportion of patients with optimal adherence included 80% (n=78/98) of those with an active account who did not enter height measurements and 89% (n=113/127) of those who did. There was a significant and positive pre-post app effect on adherence (p<0.01) in patients with an active account. Our results show that using the growzen™ buddy app has a rapid and positive impact on adherence to r-hGH treatment and patients who were more engaged with the app demonstrated better adherence.